Expression, purification and preliminary crystallographic analysis of the cryptic polo-box domain of Caenorhabditis elegans ZYG-1 - Shimanovskaya, Ekaterina (International Union of Crystallography, 2014)
ZYG-1 is a polo-like kinase essential for centriole assembly in Caenorhabditis elegans. The targeting of ZYG-1 to nascent centrioles is via its central cryptic polo-box (CPB) domain. To shed light on the molecular basis of ZYG-1 recruitment, it is necessary to obtain structural knowledge of the ZYG-1 CPB. Here, the expression, purification and preliminary crystallographic analysis of the ZYG-1 CPB are reported. The protein was overexpressed in Escherichia coli strain BL21 (DE3), purified by multi-step chromatography and crystallized using the vapour-diffusion method. Crystals of the wild-type protein exhibited an order–disorder pathology, which was solved by reductive lysine methylation. A complete anomalous data set was collected to 2.54 Å resolution at the Se K edge (λ = 0.9792 Å). The crystal belonged to space group P2, with unit-cell parameters a = 53.3, b = 60.09, c = 87.51 Å, β = 93.31°. There were two molecules in the asymmetric unit.